STRATEGI BRAND EXPERIENCE, BRAND IMAGE DAN CUSTOMER SATISFACTION DALAM MENINGKATKAN CUSTOMER LOYALTY (STUDY KASUS MEREK ADIDAS) - Indrasari, Rafi; Hikmah Perkasa, Didin (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of brand experience, brand image, and customer satisfaction on customer loyalty among Adidas consumers in Jakarta amid increasing competition in the premium sportswear industry. The objective is to empirically test the contribution of these variables to loyalty formation. A quantitative survey was conducted with 200 respondents using purposive sampling, and data were analyzed through PLS-SEM. The findings reveal that all variables positively and significantly affect customer loyalty, with customer satisfaction as the strongest predictor. The results imply that sustaining product quality, service excellence, and consistent brand positioning is essential to strengthen long-term consumer loyalty.